Combining fibre rotation and fragmentation to achieve pseudo-ductile CFRP laminates. (10th May 2016) - Fuller, J.D.; Jalalvand, M.; Wisnom, M.R.
Abstract: The pseudo-ductility shown by thin ply angle-ply laminates has been coupled with the gradual fragmentation of unidirectional ( 0 ° ) plies to yield a metal-like stress–strain curve for a [ ± θ m / 0 n ] s laminate. This has led to a significant increase in pseudo-ductility than either angle-ply fibre rotation or 0 ° fragmentation have shown previously. Analytical modelling has been developed that accounts for the damage processes that contribute to the gradual failure of the 0 ° plies and predictions have been made taking into account the fragmentation, delamination and eventual failure of the laminate. Experimental results are shown to correlate well with the modelling, despite some variability in the responses. Analysis via X-ray computed tomography of tested specimens shows the progression of the fragmentation and delamination damage modes prior to laminate failure and provides an in-depth understanding of the process that leads to the demonstrated pseudo-ductile strains.